2000
DOI: 10.1161/01.cir.102.7.779
|View full text |Cite
|
Sign up to set email alerts
|

Herpesvirus Infection Accelerates Atherosclerosis in the Apolipoprotein E–Deficient Mouse

Abstract: Background-Human herpesviruses have been implicated but not proven to be involved in the etiology of atherosclerosis.To determine whether there is a causal relationship, the effect of herpesvirus infection on the development of atherosclerosis was assessed in the apolipoprotein E-deficient (apoEϪ/Ϫ) mouse. Methods and Results-In the present study, 3-to 4-week-old apoEϪ/Ϫ mice were infected with murine ␥-herpesvirus-68(MHV-68). Atheroma formation was accelerated over a 24-week period in infected apoEϪ/Ϫ mice co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
71
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(74 citation statements)
references
References 39 publications
3
71
0
Order By: Relevance
“…Inflammation, stress and infection are all known to be proatherogenic in apoE Ϫ/Ϫ mice (43)(44)(45)(46)(47)(48). In studying the possible specific actions of human CRP, it is therefore essential to be aware of, and if necessary exclude, intercurrent inflammatory pathology, such as the effects of occasional fighting (which is Cohort A 8 5 (4-7) n ϭ 4 NA 9 (5-12) n ϭ 8 11.1 (3.0-17.7) n ϭ 8 9 (5-12) n ϭ 21 NA 9 (5-12) n ϭ 11 10.9 (2.0-22.8) n ϭ 11 12 6 (3-10) n ϭ 7 NA 6 (1-8) n ϭ 18 7.8 (1.1-13.7) n ϭ 18 6 (3-11) n ϭ 17 NA 6 (4-11) n ϭ 17 17.1 (3.8-36.1) n ϭ 17, P Ͻ 0.005 16 6 (2-11) n ϭ 7 NA 6 (3-12) n ϭ 20 6.2 (1.2-14.2) n ϭ 20 6.5 (3-11) n ϭ 18 NA 6 (4-11) n ϭ 13 24.0 (9.8-31.2) n ϭ 13, P Ͻ 0.0001 20 6 (1-7) n ϭ 5 NA 4 (1-11) n ϭ 17 9.1 (1.3-12.6) n ϭ 17 5 (3-12) n ϭ 27 NA 4.5 (1-12) n ϭ 28 20.9 (1.8-41.1) n ϭ 28, P Ͻ 0.0001 Cohort B 12 NA ND 17.5 (2.9-21.9) n ϭ 5 ND 22.0 (11.2-32.6) n ϭ 5,…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation, stress and infection are all known to be proatherogenic in apoE Ϫ/Ϫ mice (43)(44)(45)(46)(47)(48). In studying the possible specific actions of human CRP, it is therefore essential to be aware of, and if necessary exclude, intercurrent inflammatory pathology, such as the effects of occasional fighting (which is Cohort A 8 5 (4-7) n ϭ 4 NA 9 (5-12) n ϭ 8 11.1 (3.0-17.7) n ϭ 8 9 (5-12) n ϭ 21 NA 9 (5-12) n ϭ 11 10.9 (2.0-22.8) n ϭ 11 12 6 (3-10) n ϭ 7 NA 6 (1-8) n ϭ 18 7.8 (1.1-13.7) n ϭ 18 6 (3-11) n ϭ 17 NA 6 (4-11) n ϭ 17 17.1 (3.8-36.1) n ϭ 17, P Ͻ 0.005 16 6 (2-11) n ϭ 7 NA 6 (3-12) n ϭ 20 6.2 (1.2-14.2) n ϭ 20 6.5 (3-11) n ϭ 18 NA 6 (4-11) n ϭ 13 24.0 (9.8-31.2) n ϭ 13, P Ͻ 0.0001 20 6 (1-7) n ϭ 5 NA 4 (1-11) n ϭ 17 9.1 (1.3-12.6) n ϭ 17 5 (3-12) n ϭ 27 NA 4.5 (1-12) n ϭ 28 20.9 (1.8-41.1) n ϭ 28, P Ͻ 0.0001 Cohort B 12 NA ND 17.5 (2.9-21.9) n ϭ 5 ND 22.0 (11.2-32.6) n ϭ 5,…”
Section: Discussionmentioning
confidence: 99%
“…However, one study demonstrated that herpes infection accelerates atherosclerosis in apolipoprotein E-deficient mice, through an impairment of the eNOS pathway (72). We have recently demonstrated severe impairment of eNOS in endothelial cells infected with CMV, and that this is due to increased levels of ADMA, the competitive inhibitor of NOS.…”
Section: Impairment Of the Nitric Oxide Synthase Pathway In Cmv-inducmentioning
confidence: 92%
“…11 HSV1 DNA has been found in some but not all samples of carotid atherosclerotic lesions. 12,13 The recurrent outbreaks associated with HSV infection and high population prevalence of exposure have made it an interesting target for epidemiological study.…”
Section: Herpesvirus Familymentioning
confidence: 99%
“…12,13 The recurrent outbreaks associated with HSV infection and high population prevalence of exposure have made it an interesting target for epidemiological study. 11 For CMV, evidence for involvement in vascular disease has been garnered from polymerase chain reaction (PCR) detection of CMV DNA in atherosclerotic lesions. For example, Hendrix et al found CMV DNA in 90% of advanced atherosclerotic lesions compared with only 50% of control patients with no or minimal atherosclerosis.…”
Section: Herpesvirus Familymentioning
confidence: 99%